A Influência do Capital Humano na Qualidade de Serviços: Um Estudo em Instituições Financeiras no Segmento de Micro e Pequenas Empresas Paranaenses - Vieira, Ronaldo Perez (2018)
This study investigated the human capital influence on the quality of services in the bank service sector to micro and small companies in Parana. The research was carried out with the employees of financial institutions that serve micro and small companies from several economics sectors in the State of Parana. It was use the replication of the collect instrument of the survey applied in the European country of Andorra, from the authors Mariño-Mesías, Rodríguez-Antón & Rubio-Andrada (2015). The quantitative evaluation used in the descriptive statistics was carried out through the use of IBM SPSS Statistics software version 22 and to the Structures Equations Model was used the SmartPLS 3 Software. The results shown demonstrated high level of significance and strong relation in the degree of influence of human capital in the quality of services.